The nature of the private initiatives and the control of the decisions of the Public Administration - Shimabukuro Tokashiki, Néstor (2017)
Despite the evolution of the private investment promotion regime in relation to investment projects under private initiatives, there are many shortcomings in its regulation, especially at the evaluation stage, which creates serious disincentives for attracting private investors. One of these defects derives from its consideration as requests of graces and of how the Administration understands this type of petitions. Having this problem in mind, we propose a rereading of the nature of private initiatives to ensure that decisions taken by the Public Administration in this regard are subject to a true control of legality.